DIFFERENCES OF TODDLER OBESITY BASED ON EXCLUSIVE BREASTFEEDING HISTORY IN TEGALREJO HEALTH CENTER, YOGYAKARTA - Suci Musvita Ayu; Arini Mayang Fa'uni (Epidemiology and Society Health Review (ESHR), 2021)
Background: Obesity is a global problem and continues to affect low and middle-income countries, mainly urban areas. In Indonesia, the obesity rate of children was 11.5% and was ranked 21st in the world by 2016. Even according to WHO, the number of obese children will continue to increase every year. Several studies have shown that a history of exclusive breastfeeding can reduce the risk of obesity in toddlers. This study aimed to determine the differences in the obesity status of children under five based on a history of exclusive breastfeeding in the Tegalrejo Health Center, Yogyakarta City.Methods: This research employed an analytical observational study with a case-control design. The research sample consisted of 34 toddlers aged 6-24 months, calculated using the difference of two proportions: 17 cases of obese children under five and 17 controls under five who were not obese. A questionnaire was used to collect the data. A Chi-square test was used to analyse the data.Results: There were children under five without exclusive breastfeeding in the group of as many as 41.7% and 29.4% in the control group. 52,9% of children in the case group had exclusive breastfeeding, and 70% in the control group. The bivariate analysis showed no difference in the obesity status of children under five based on a history of exclusive breastfeeding with a value of p = 0.480 and OR = 2.133 (95% CI = 0.519-8.751).Conclusions: There was no difference in the obesity status of children under five based on a history of exclusive breastfeeding, but children without a history of exclusive breastfeeding were 2.133 times more likely to have obesity than children with exclusive breastfeeding.